Regional Governance im „Schatten der Hierarchie”: Theoretische Überlegungen und ein Beispiel aus Schleswig-Holstein - Diller, Christian (Raumforschung und Raumordnung | Spatial Research and Planning, 2004)
Differing from the requirements implied in the term “autonomous regional development”, regional governance is almost always dependent on public support. This raises the question of the appropriate “state-run guidance” for these regional governance structures. The article outlines the particularly efficient governance mode of “network-based co-operative negotiations in the shadow of hierarchy” as well as some typical forms of action and problems of state and regional planning in the support of regional governance. Taking the concepts for cities and their surrounding areas in Schleswig-Holstein as examples, it is shown that the careful construction of a “shadow of hierarchy” is a central precondition for successful regional co-operation. It is exactly the combination of public policy- and development policy aspects that makes this type of regional governance attractive and qualifies state and regional planning as its mentor.